ИССЛЕДОВАНИЕ ПОГРЕШНОСТИ УСТАНОВКИ ЧАСТОТЫ СИНТЕЗАТОРОВ ЧАСТОТНО-ФАЗОВЫХ СИСТЕМ С ИСПОЛЬЗОВАНИЕМ LABVIEW - Зайцев , Е.А. (Інститут електродинаміки НАН України, Київ, 2014)
This paper is devoted to software realization in NI LabVIEW frequency synthesizer for multi frequency phase measurement system of the measurement distances and linear motion of technical objects. It is shown that in these devices, laser voltage is generated by a digital frequency synthesizer, and informative parameters of the system are determined as a result of multiplying the voltage of the signal and local oscillator with subsequent digital processing based on the Fourier and Hilbert transform. A block diagram of a frequency synthesizer based on an integrated circuit AD9851. The structure and main modules of developed software is represented in the article. Developed prototype based on the proposed block diagram. The results of experimental investigations of the model and the layout of the frequency synthesizer. References 10, figures 4.